Research on music education simulation based on interactive experience of virtual and reality - Wanchen Li (Systems and Soft Computing, 2025)
This study focuses on the music education simulation based on virtual and real interactive experience. By deeply analyzing the application status of virtual reality technology in music education, it reveals the improvement of students' learning efficiency and effect. The study first collected and analyzed a large amount of music education data, and found that most families' investment in music education accounted for 5 % -10 % of the family income, showing the great potential of the music education market. Among them, preschool children and K12 users are the key target customers of the music education market, and their needs for music education methods are increasingly diversified. Subsequently, this study crafted a music education simulation system grounded in virtual reality technology, affording students the opportunity to engage and express themselves by simulating authentic music scenes and instruments within a virtual realm. Through comparative experimentation, we discovered that students utilizing virtual reality technology exhibited superior comprehension of musical instrument principles, mastery of musical expression, and learning efficiency compared to traditional teaching methods. Specifically, students using virtual reality had a 30 percent better accuracy in mastering the principle of Musical Instruments, increased the richness of musical expression by 25 percent, and their learning progress was nearly twice faster than traditional methods. In addition, this study also collected student feedback on the VR music education system through questionnaires and interviews. The results show that most students have a positive attitude towards this novel teaching method, and they believe that this method can better stimulate the interest in learning and improve the learning effect. To sum up, the music education simulation based on virtual and real interactive experience has significant advantages and potential, and is expected to become an important development direction in the field of music education in the future.